ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT UP AH PEKERJA SEKTOR INFORMAL DI KOTA SURAKARTA - Setyawan, Anton Agus; Mujiyati, Mujiyati (Universitas Muhammdaiyah Surakarta, 2006)
The development of informal sector in many cities in Indonesia, interests many scholars to analyse it. This research tries to describe and analyse the phenomena of under employment and gender discrimination in the informal sector at Surakarta. The research aims is to analyse the effects of education level, work experience and gender to productivity. The measurement of productivity uses level of income. This research tries to test the model proposed by Mincer (1974) and Jones (2001). The model contains of four variables, they are level of education, work experience and gender as the independent variable, while level of income is the dependent variable. To test our hypotheses we use double log econometric models.The setting of this research is micro retail entrepreneur or in Indonesia they called PKL. PKL, which become our respondents are those who locate in three PKL centre in Surakarta. Their location at around Monument 45, Manahan Stadium and Kotta Barat field. Our sampling method is purposive-sampling method and we interviewed 100 respondents to complete the data. The result shows that there are no positive correlation between level of education and gender to level of income. While work experience seems to have a positive effect to level of income. It concludes that there is a under employment phenomena in informal sector at Surakarta. While the hypotheses which said that there are gender discrimination is not supported.